The Baha’i Religion: Maqasid Syariah of Social Religious Frictions in Indonesia - Muzammil, Shofiyullah (FIKRAH, 2023)
The contestation of conversation about the Baha'i religious group in Indonesia continues from time to time. In valuable retrospect, there has been much debate that characterizes the existence of the Baha'i group. As a result, it is very unfortunate that there are many frictions caused by socio-religious friction in the social sphere. This has led to many assumptions about religious freedom in Indonesia, which are increasingly showing a repressive trend. The author is interested in analyzing the various frictions that arise between the gaps in religious plurality in Indonesia, both pragmatic and paradigmatic. In addition, the author wants to examine how the role of the government can break the deadlock of friction. The research was conducted with a qualitative analysis oriented toward a literature review and Maqasid Syariah as a theoretical perception. Exploration research focuses on various phenomena that occur around the presence of Baha'is in Indonesia and how potential conflicts can arise in them. This research proves that the state needs to be present to accommodate various religions and coexist by prioritizing the concept of benefit for all citizens. In addition, the role of society in maintaining multicultural values must be initiated more intensely and in a dialogical manner.